Vybrané problémy realizace emise podnikových dluhopisů - Tetřevová, Liběna; Hávová, Eva (Univerzita Pardubice, 2000)
The article deals with choice problems of decision and direction of issuing. The process of decision - taking and control of the issuing are very important.The issuer has to make decision on using of an intermediator, on the range of its services and he or she to choose the most convenient subject. The issuing of corporate bonds is time and money consuming and requires good knowledge of law and situation on the capital market. And that is why the most of financial managers prefer issuing organized by intermediators. The issuing of corporate bonds involves managing of many activities either with or without an intermediator. Our attention is paid especially to the first steps of preparation of issue - formation of financial project and rating of issuer.
Keywords: Emise; dluhopisy; podniky; rozhodovací procesy; realizace